2023
DOI: 10.1038/s41598-023-40838-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic signature of stroke recurrence after transient ischemic attack

F. Purroy,
A. Ois,
M. Jove
et al.

Abstract: While TIA patients have transient symptoms, they should not be underestimated, as they could have an underlying pathology that may lead to a subsequent stroke: stroke recurrence (SR). Previously, it has been described the involvement of lipids in different vascular diseases. The aim of the current study was to perform a lipidomic analysis to identify differences in the lipidomic profile between patients with SR and patients without. Untargeted lipidomic analysis was performed in plasma samples of 460 consecuti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…On the other hand, triacylglycerol species (TG [48:1] and [48:2], VIP > 2; TG [50:3], [53:3] and [56:6], VIP > 1.5, Figure 1b) were significantly decreased in patient serums compared to control serums (Figures 2 and 3), while TG (52:4) and TG (54:3) (VIP > 1.5, Figure 4b) were decreased in stroke thrombi compared to patient serums (Figures 5 and 6). This is in accordance with previous studies, characterizing TG as bioenergetic compounds of lipid droplets that are also present in neural cells, which were reported to have low abundance in plasma patients having stroke recurrence after transient ischemic attack, possibly due to low accumulation or formation of cerebral lipid droplets as a product of a defective ischemia-associated stress response [48].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, triacylglycerol species (TG [48:1] and [48:2], VIP > 2; TG [50:3], [53:3] and [56:6], VIP > 1.5, Figure 1b) were significantly decreased in patient serums compared to control serums (Figures 2 and 3), while TG (52:4) and TG (54:3) (VIP > 1.5, Figure 4b) were decreased in stroke thrombi compared to patient serums (Figures 5 and 6). This is in accordance with previous studies, characterizing TG as bioenergetic compounds of lipid droplets that are also present in neural cells, which were reported to have low abundance in plasma patients having stroke recurrence after transient ischemic attack, possibly due to low accumulation or formation of cerebral lipid droplets as a product of a defective ischemia-associated stress response [48].…”
Section: Discussionsupporting
confidence: 93%
“…Phosphatidyl-cholines are components of plasma lipoproteins regulating circulating lipoprotein levels such as low-density (VLDLs) and high density (HDL) lipoproteins 113 . Consequently, several studies demonstrated phosphatidyl-cholines related to a decreased risk for diabetes, cardiovascular disease and stroke [ 119 121 ]. Triacylglycerides …”
Section: Ongoing 3pm Research Towards Vulnerable Groups In the Popula...mentioning
confidence: 99%
“…Consistent with this data, an association between hypertriglyceridemia in diabetic patients and lower-extremity amputation risk has been shown [ 122 ]; blood triglycerides have been demonstrated as reliable pre/diabetes biomarkers [ 123 ]. In parallel, specific lipid profiles were demonstrated to be linked to high-risk for ischemic stroke [ 121 ].…”
Section: Ongoing 3pm Research Towards Vulnerable Groups In the Popula...mentioning
confidence: 99%